Human fatty acid synthase: Assembling recombinant halves of the fatty acid synthase subunit protein reconstitutes enzyme activity - Jayakumar, Arumugam (The National Academy of Sciences of the USA, 1997)
Our model of the native fatty acid synthase (FAS) depicts it as a dimer of two identical multifunctional proteins (M(r) ≈ 272,000) arranged in an antiparallel configuration so that the active Cys-SH of the β-ketoacyl synthase of one subunit (where the acyl group is attached) is juxtaposed within 2 Å of the pantetheinyl-SH of the second subunit (where the malonyl group is bound). This arrangement generates two active centers for fatty acid synthesis and predicts that if we have two appropriate halves of the monomer, we should be able to reconstitute an active fatty acid-synthesizing site. We cloned, expressed, and purified catalytically active thioredoxin (TRX) fusion proteins of the NH(2)-terminal half of the human FAS subunit protein (TRX-hFAS-dI; residues 1–1,297; M(r) ≈ 166) and of the C-terminal half (TRX-hFAS-dII-III; residues 1,296–2,504; M(r) ≈ 155). Adding equivalent amounts of TRX-hFAS-dI and TRX-hFAS-dII-III to a reaction mixture containing acetyl-CoA, malonyl-CoA, and NADPH resulted in the synthesis of long-chain fatty acids. The rate of synthesis was dependent upon the presence of both recombinant proteins and reached a constant level when they were present in equivalent amounts, indicating that the reconstitution of an active fatty acid-synthesizing site required the presence of every partial activity associated with the subunit protein. Analyses of the product acids revealed myristate to be the most abundant with small amounts of palmitate and stearate, possibly because of the way the fused recombinant proteins interacted with each other so that the thioesterase hydrolyzed the acyl group in its myristoyl state. The successful reconstitution of the human FAS activity from its domain I and domains II and III fully supports our model for the structure–function relationship of FAS in animal tissues.